2012
DOI: 10.1111/j.1365-2788.2011.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adult functional outcome in adolescents receiving special educational assistance

Abstract: Background  This study investigates the role of IQ, autistic traits and challenging behaviours in affecting adult outcomes among adolescents who receive special educational assistance. Methods  A total of 58 participants were recruited from an ongoing longitudinal study. All received assessments of IQ, behavioural patterns (using the Childhood Behaviour Checklist – CBCL) and autistic traits (using the Social Communication Questionnaire – SCQ) during adolescence and were followed up 6 years later (at a mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Although the absolute differences in PANSS scores were relatively small, the effect of having morbid psychopathology in adolescents is high. 26,27 We have previously shown that functional outcome in this cohort is highly variable and is related to intellectual ability and behavioural difficulties; 28 we did not, however, consider ongoing psychopathology in that report. The findings presented here suggest that this matter merits further attention, as much of the general psychopathology was accounted for by anxiety-and mood-related symptoms, and effective treatments for these symptoms are well established.…”
Section: Discussionmentioning
confidence: 92%
“…Although the absolute differences in PANSS scores were relatively small, the effect of having morbid psychopathology in adolescents is high. 26,27 We have previously shown that functional outcome in this cohort is highly variable and is related to intellectual ability and behavioural difficulties; 28 we did not, however, consider ongoing psychopathology in that report. The findings presented here suggest that this matter merits further attention, as much of the general psychopathology was accounted for by anxiety-and mood-related symptoms, and effective treatments for these symptoms are well established.…”
Section: Discussionmentioning
confidence: 92%
“…Unfortunately, social anxiety in adolescents with ASD can impede adolescent developmental tasks, adaptive behaviors, and independent function in adult life (e.g. forming love relationships, and employment) (McGeowen et al, 2013 ; Picci & Scherf, 2015 ; Taylor & Seltzer, 2012 ). Finding evidence of an effective way, without medication, to address stress in young adults with ASD, will have implications for overall wellness and quality of life (Hong et al, 2016 ; Shattuck et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%